Estimation of genetic parameter for wool traits in FGF5 gene-edited Chinese Merino sheep - Yue, Chengguang; Kang, Jie; Liu, Chenxi; Han, Bin; Li, Zhonghui; Li, Wenrong (Frontiers in Animal Science, 2026)
IntroductionWe previously edited the fibroblast growth factor 5 (FGF5) gene to improve wool quality and increase wool production. However, the current population of FGF5 gene-edited sheep faces low breeding efficiency during expansion. To address this challenge, we constructed multi-trait animal models to estimate the genetic parameters of key wool traits.MethodsPhenotypic data were collected from 281 yearling FGF5 gene-edited fine-wool sheep at the Sheep Breeding Base of the Xinjiang Academy of Animal Science. Two relationship matrices were constructed: one based on pedigree information (LM_A) and another combining pedigree and genomic information (LM_H). Genetic parameters were estimated for staple length (SL), straightened length (TL), fiber diameter (FD), and greasy fleece weight (GFW).ResultsHeritability estimates for SL (0.401, 0.380), TL (0.265, 0.309), and FD (0.240, 0.302) using LM_A and LM_H were moderate, while GFW (0.153, 0.164) showed low heritability. Strong positive genetic correlations were observed among SL, TL, and GFW, with correlation coefficients ranging (0.518 - 0.969). Compared with LM_A, LM_H produced heritability estimates with smaller standard errors.DiscussionOverall, the LM_H approach under the multi-trait animal model provides more accurate estimates of genetic parameters for wool traits. Our findings provide a basis for genetic estimation in FGF5 gene-edited fine-wool sheep and support the development of genetic evaluation for this population.